Casuistry and Early Modern Spanish Literature - Bidwell-Steiner, Marlen (Foro Hispánico, 2022)
Investigating the importance of casuistry in a variety of genres in early modern Spain, this volume fills a significant gap in the scholarship, and calls for a re-thinking of the development of early modern Spanish literature and thought.; Readership: Renaissance and Early Modern scholars and students interested in the rise of imaginative literature and its embeddedness in pre-modern Spanish society. It will also appeal to Religious Studies scholars.